N-Tox® - Early warning of nitrification toxicity for activated sludge treatment - Callister, S.; Stephenson, Tom; Butler, M. D.; Cartmell, Elise (Cranfield University, 2006)
N-Tox® is a new technique for evaluating the nitrification efficiency in industrial or municipal activated sludge systems, using direct measurement of nitrous oxide (N20) as an indicator of nitrification failure. Research using pilot-scale activated sludge plants treating real settled wastewater has demonstrated that detection of increased N2O concentration in the aeration tanks by N-Tox® is able to provide early warning of nitrification failure. The N-Tox® monitor relies on non-invasive gas-phase detection which avoids sampling of activated sludge and eliminates associated probe fouling problems and maintenance issues. Nitrification failure detection by N-Tox® is rapid, giving plant operators the time to take remedial action before possible release of ammonia. Recently presented data has shown the effectiveness of N-Tox® in providing early warning of nitrification inhibition following loss of aeration and ammonia overloading events. New data is now presented to demonstrate the effectiveness of N-Tox® in providing early warning of nitrification failure for a number of well-known toxic chemicals. These include the organic compound phenol, the nitrification suppressant allylthiourea (ATU) and the inorganic fungicide and herbicide, sodium azide. N-Tox® was able to detect nitrification failure when the first step of nitrification was inhibited, resulting in a rise in effluent ammonia, and when the second step was inhibited, resulting in a rise in effluent nitrite. The pattern of N2O emission indicated the failure mode: a sharp peak indicated ammonia breakthrough whereas a sustained increase in N2O indicated nitrite formation. The N-Tox® device can also be used to quantify emissions of N2O, a powerful greenhouse gas, from wastewater treatme
Keywords: N2O; Nitrous Oxide; Nitrification; Inhibition; Toxicity; Monitor; Greenhouse Gas